Higher exhaled nitric oxide at 6 weeks of age is associated with less bronchiolitis and wheeze in the first 12 months of age. Issue 11 (3rd December 2021) - Da Silva Sena, Carla Rebeca; de Queiroz Andrade, Ediane; de Gouveia Belinelo, Patricia; Percival, Elizabeth; Prangemeier, Benjamin; O'Donoghue, Christopher; Terry, Sandrine; Burke, Tanya; Gunning, William; Murphy, Vanessa E; Robinson, Paul D; Sly, Peter D; et al.
Abstract : Background: Nitric oxide in exhaled air (eNO) is used as a marker of type 2 immune response-induced airway inflammation. We aimed to investigate the association between eNO and bronchiolitis incidence and respiratory symptoms in infancy, and its correlation with eosinophil protein X (EPX). Methods: We followed up infants at 6 weeks of age born to mothers with asthma in pregnancy and measured eNO during natural sleep using a rapid response chemiluminescense analyser (CLD88; EcoMedics), collecting at least 100 breaths, interpolated for an expiratory flow of 50 mL/s. EPX normalised to creatinine was measured in urine samples (uEPX/c). A standardised questionnaire was used to measure symptoms in first year of life. Associations were investigated using multiple linear regression and robust Poisson regression models. Results: eNO levels were obtained in 184 infants, of whom 125/184 (68%) had 12 months questionnaire data available and 51/184 (28%) had uEPX/c measured. Higher eNO was associated with less respiratory symptoms during the first 6 weeks of life (n=184, ß-coefficient: –0.49, 95% CI –0.95 to –0.04, p=0.035). eNO was negatively associated with uEPX/c (ß-coefficient: –0.004, 95% CI –0.008 to –0.001, p=0.021). Risk incidence of bronchiolitis, wheeze, cold or influenza illness and short-acting beta-agonist use significantly decreased by 18%–24% for every unit increase in eNO ppb. Conclusion: Higher eNO levels at 6 weeks of age may be a surrogate for an altered immune response that is associated with less respiratory symptoms in the first year of life.